2018
DOI: 10.1016/j.repbio.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin supplementation during in vitro embryo culture improves developmental competence of bovine embryos produced using sex-sorted semen

Abstract: Using sex-sorted semen to produce offspring of desired sex is associated with reduced developmental competence in vitro and lower fertility rates in vivo. The objectives of the present study were to investigate the effects of exogenous follistatin supplementation on the developmental competence of bovine embryos produced with sex-sorted semen and possible link between TGF-β regulated pathways and embryotrophic actions of follistatin. Effects of follistatin on expression of cell lineage markers (CDX2 and Nanog)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Follistatin transcripts were higher in BCB positive (BCB+) high‐quality oocytes compared to BCB− oocytes (Ashry et al, 2015). Functional studies revealed that maternally derived follistatin is essential for early development in bovine preimplantation embryos and that exogenous follistatin supplementation during the first 72 hr of in vitro embryo culture improves the developmental capacity of bovine (Ashry et al, 2015; Ashry, Lee, Folger, Rajput, & Smith, 2018; Ashry, Rajput, et al, 2018; Lee, Bettegowda, Wee, Ireland, & Smith, 2009; Patel et al, 2007; Zhenhua et al, 2017) and Rhesus macaque embryos (VandeVoort, Mtango, Lee, Smith, & Latham, 2009). Interestingly, in vitro‐produced (IVP) blastocysts derived from embryos treated with follistatin exhibit higher trophectoderm (TE) cell numbers and increased expression of caudal‐type homeobox 2 ( CDX2 ) messenger RNA (mRNA; Lee et al, 2009; Zhenhua et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Follistatin transcripts were higher in BCB positive (BCB+) high‐quality oocytes compared to BCB− oocytes (Ashry et al, 2015). Functional studies revealed that maternally derived follistatin is essential for early development in bovine preimplantation embryos and that exogenous follistatin supplementation during the first 72 hr of in vitro embryo culture improves the developmental capacity of bovine (Ashry et al, 2015; Ashry, Lee, Folger, Rajput, & Smith, 2018; Ashry, Rajput, et al, 2018; Lee, Bettegowda, Wee, Ireland, & Smith, 2009; Patel et al, 2007; Zhenhua et al, 2017) and Rhesus macaque embryos (VandeVoort, Mtango, Lee, Smith, & Latham, 2009). Interestingly, in vitro‐produced (IVP) blastocysts derived from embryos treated with follistatin exhibit higher trophectoderm (TE) cell numbers and increased expression of caudal‐type homeobox 2 ( CDX2 ) messenger RNA (mRNA; Lee et al, 2009; Zhenhua et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence supports an embryotrophic role of follistatin in IVF embryos [ 11 15 , 27 , 28 ]. Exogenous follistatin supplementation (10ng/ml) during IVC1, improved blastocyst rates of bovine SCNT embryos [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in our laboratory showed that exogenous follistatin supplementation during in vitro embryo culture improves the developmental competence of bovine preimplantation embryos produced under different conditions. These include conventional IVF [ 12 14 ], IVF using poor quality oocytes [ 11 ], and IVF using sex sorted semen [ 15 ]. In general, follistatin treatment increases blastocyst rates, CDX2 expression and trophectoderm (TE) cell number on day 7 of development.…”
Section: Introductionmentioning
confidence: 99%